2020
DOI: 10.3390/molecules25112494
|View full text |Cite
|
Sign up to set email alerts
|

Towards a High-Power Si@graphite Anode for Lithium Ion Batteries through a Wet Ball Milling Process

Abstract: Silicon-based anodes are extensively studied as an alternative to graphite for lithium ion batteries. However, silicon particles suffer larges changes in their volume (about 280%) during cycling, which lead to particles cracking and breakage of the solid electrolyte interphase. This process induces continuous irreversible electrolyte decomposition that strongly reduces the battery life. In this research work, different silicon@graphite anodes have been prepared through a facile and scalable ball milling synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 58 publications
3
21
0
Order By: Relevance
“…Deploying the Si/graphite or carbon composite anode has been attempted to relieve the volume-change-driven instability of Si anodes and has recently been suggested for rapid high-energy-density realization in the present application. The graphite blending system can achieve both high energy density and stable cyclability, unlike independent graphite or Si anodes. Therefore, we prepared a composite anode composed of Si (or Si@pGN) and an AG mixture with a 2:8 weight ratio of Si (or Si@pGN) to AG (denoted as Si/AG28 and Si@pGN/AG28).…”
Section: Resultsmentioning
confidence: 99%
“…Deploying the Si/graphite or carbon composite anode has been attempted to relieve the volume-change-driven instability of Si anodes and has recently been suggested for rapid high-energy-density realization in the present application. The graphite blending system can achieve both high energy density and stable cyclability, unlike independent graphite or Si anodes. Therefore, we prepared a composite anode composed of Si (or Si@pGN) and an AG mixture with a 2:8 weight ratio of Si (or Si@pGN) to AG (denoted as Si/AG28 and Si@pGN/AG28).…”
Section: Resultsmentioning
confidence: 99%
“…The lower cut-off voltage was fixed at 0.05 V to limit the volume expansion experienced by silicon during prolonged cycling at low potentials that leads to poor stability [ 15 ]. During lithiation, below 0.2 V, the intercalation of lithium into graphite [ 29 , 30 ] and Si alloy formation take place. It was reported that, firstly, Li ~2 Si is formed at ca.…”
Section: Resultsmentioning
confidence: 99%
“…Direct milling, chemical vapor deposition (CVD) and liquid-phase assembly are among the reported methods to prepare Si/graphite composites. 78 For example, Cabello et al 81 used a wet ball milling process to prepare a high-power Si@graphite composite. Here, an efficient dispersion and distribution of the particles is achieved with the addition of isopropyl alcohol during the synthesis procedure, and the use of few layer graphene as a conductive agent results in an electrode with an optimal microstructure that is able to mitigate Si volume changes during cycling.…”
Section: Si Based Anode Materialsmentioning
confidence: 99%